Country risk perceptions and foreign direct investment in emerging market economies: a panel data analysis / Debabrata Mukhopadhyay and Dipankar Das - Mukhopadhyay, Debabrata; Das, Dipankar (Accounting Research Institute (ARI), 2020)
This study aimed at examining the impact of major political risks, financial risks and economic factors on FDI inflows in emerging economies along with basic economic fundamentals such as institutional variables namely, per capita GDP, per capita electric consumption, trade openness and real rate of interest. This study followed a static panel data approach in studying the impact of these crucial variables on FDI inflows in fifteen major emerging economies for the period 2000 to 2014. Risk perceptions i.e., political risks and other risk perception data were collected from the International Country Risk Guide (ICRG) provided by the Political Risk Services (PRS) Group. Our results demonstrate that risk perception components such as government stability, quality bureaucracy etc., are statistically significant with expected signs in explaining variations in FDI inflows in the major emerging countries.